Influence of internal factors on the use of equity- and mezzanine-based financing in family firms - Ann-Kristin Achleitner; Eva Lutz; Stephanie Schraml (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
The paper analyzes internal factors which influence the use of equity - and mezzanine-based financing instruments in German privately held family firms. Based on a sample of 195 surveys of family firms, we investigate the impact of family specific goals and corporate governance structures on the use of financial instruments such as retained earnings, private equity and silent partnerships. We find that family goals have a complex impact on the decision to use or not to use these instruments and parallel existing goals can result in diverging financing preferences. Furthermore, we find that the impact of corporate governance structures on financing decisions is mainly driven by the existence of an advisory board and the involvement of external managers in the management board. Our findings contribute to a better understanding of financing decisions in family firms and demonstrate the necessity to include family firm specific characteristics such as family goals and corporate governance structures in the analysis of financing decisions.
Keywords: G32; G30; G24; M13; 330; entrepreneurial finance; family firms; equity; mezzanine; retained earnings; private equity; silent partnership